ANSWER
B. –4, –3, 0, 5
EXPLANATION
The general formula for the sequence is:
![f(n)=n(n-2) - 3](https://img.qammunity.org/2020/formulas/mathematics/high-school/3cj3x9599uwkwkjkdyve4d4wftjwpi5cc7.png)
To find the first term we substitute n=1
![f(1)=1(1 - 2) - 3 = - 4](https://img.qammunity.org/2020/formulas/mathematics/high-school/8znlggl7r8wywiiiwifzb6l3b060ufg9l2.png)
To find the second term, we substitute n=2
![f(2)=2( 2-2) - 3 = - 3](https://img.qammunity.org/2020/formulas/mathematics/high-school/gxcrkstus2d43875w2ax1q91y6umru0hg4.png)
To find the third term,we put n=3;
![f(3)=3(3-2) - 3 = 0](https://img.qammunity.org/2020/formulas/mathematics/high-school/tl2euqvjcop62dcz6gl6m5waevwfuyonqg.png)
To find the fourth term, we put n=4
![f(n)=4(4-2) - 3 = 5](https://img.qammunity.org/2020/formulas/mathematics/high-school/kc82ufl0efwvi2x624df5z8rm03i5zq4ge.png)
The correct choice us B